A modeling study on alleviating uneven defrosting for a vertical three-circuit outdoor coil in an air source heat pump unit during reverse cycle defrosting - Song, Mengjie; Xia, Liang; Deng, Shiming (Elsevier, 2016)
Reverse cycle defrosting is the most widely used standard defrosting method for air source heat pump (ASHP) units. It was suggested in previous experimental studies that downwards flowing of the melted frost over a vertical multi-circuit outdoor coil in an ASHP unit has negative effects on reverse cycle defrosting performance. To quantitatively study the negative effects, an experimental study and a modeling study on draining away locally the melted frost for an experimental ASHP unit with a three-circuit outdoor coil were carried out and separately reported. However, for exiting ASHP units, it is hardly possible to install water collecting trays between circuits. To alleviate uneven defrosting for a vertical multi-circuit outdoor coil in an existing ASHP unit, an effective alternative is to vary the heat supply to each refrigerant circuit by varying the opening values of modulating valves installed at an inlet pipe to each circuit. In this paper, a modeling study on varying heat (via refrigerant) supply to each refrigerant circuit in a three-circuit outdoor coil to alleviate uneven defrosting is reported. Finally, in the designed three study cases, defrosting energy use could be decreased to 94.6%, as well as a reduction of 7 s in defrosting duration by fully closing the modulating valve on the top circuit when its defrosting terminated.